2013
DOI: 10.1007/s00221-013-3744-5
|View full text |Cite
|
Sign up to set email alerts
|

Eyes wide open: enhanced pupil dilation when selectively studying important information

Abstract: Remembering important information is imperative for efficient memory performance, but it is unclear how we encode important information. The current experiment evaluated two non-exclusive hypotheses for how learners selectively encode important information at the expense of less important information (differential resource allocation and information reduction). To evaluate these hypotheses, we measured changes in learners’ pupil diameter and fixation durations while participants performed a selectivity task th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 31 publications
8
52
0
Order By: Relevance
“…These effects have been shown using a variety of memory tests including free and serial recall, and recognition memory (Adcock et al, 2006;Eysenck & Eysenck, 1982;Harley, 1965;Loftus & Wickens, 1970;Madan, Caplan, Lau, & Fujiwara, 2012;Spaniol, Schain, & Bowen, 2013;Wolosin, Zeithamova, & Preston, 2012). Furthermore, these findings extend to value-based learning where points are used instead of monetary incentives (Ariel & Castel, 2014;Castel, 2007;Castel, Benjamin, Craik, & Watkins, 2002;Castel, Murayama, Friedman, McGillivray, & Link, 2013;Friedman & Castel, 2011;Soderstrom & McCabe, 2011). Taken together these findings suggest that people are acting to maximize reward and are able to allocate cognitive resources during learning so that higher value items are better encoded than lower value items.…”
supporting
confidence: 54%
“…These effects have been shown using a variety of memory tests including free and serial recall, and recognition memory (Adcock et al, 2006;Eysenck & Eysenck, 1982;Harley, 1965;Loftus & Wickens, 1970;Madan, Caplan, Lau, & Fujiwara, 2012;Spaniol, Schain, & Bowen, 2013;Wolosin, Zeithamova, & Preston, 2012). Furthermore, these findings extend to value-based learning where points are used instead of monetary incentives (Ariel & Castel, 2014;Castel, 2007;Castel, Benjamin, Craik, & Watkins, 2002;Castel, Murayama, Friedman, McGillivray, & Link, 2013;Friedman & Castel, 2011;Soderstrom & McCabe, 2011). Taken together these findings suggest that people are acting to maximize reward and are able to allocate cognitive resources during learning so that higher value items are better encoded than lower value items.…”
supporting
confidence: 54%
“…Each of the two full practice lists included recall tests with feedback. Prior work has shown that selectivity is typically stronger on the third and subsequent lists than on the first two lists (Ariel and Castel, 2014; Castel, 2008; McGillivray and Castel, 2011). Thus, we assumed that by presenting two full lists prior to scanning, strategy use would be relatively well established and consistent in the scanner.…”
Section: Methodsmentioning
confidence: 99%
“…Each of the two full practice lists included recall tests with feedback. Prior work has shown that selectivity is typically stronger on the third and subsequent lists than on the first two lists (Ariel & Castel, 2014; Castel, 2008; McGillivray & Castel, 2011). Thus, we assumed that by presenting two full lists prior to scanning, strategy use would be relatively well established and consistent in the scanner.…”
Section: Methodsmentioning
confidence: 99%
“…The VDR paradigm involves having participants study a list of words paired with point values, with the participants’ goal being to maximize the total score, which is the sum of the values associated with recalled words. A number of behavioral studies (e.g., Ariel & Castel, 2014; Castel et al, 2002; Castel, Farb, & Craik, 2007; Castel, Murayama, Friedman, McGillivray, & Link, 2013; Hanten et al, 2007; Loftus & Wickens, 1970; Soderstrom & McCabe, 2011; Watkins & Bloom, 1999) have shown that words that are arbitrarily determined to be valuable (via high point values) tend to be recalled better than words that are arbitrarily assigned lower values. However, prior studies with this paradigm have been limited in fully explaining the effect on a mechanistic level, with explanations ranging from differential forms of rehearsal, use of imagery, and strategic encoding and retrieval operations.…”
mentioning
confidence: 99%